Interactions Between Cells of Sulfobacillus thermosulfidooxidans and Leptospirillum ferriphilum During Pyrite Bioleaching - Li, Qian; Zhu, Jianyu; Li, Shoupeng; Zhang, Ruiyong; Xiao, Tangfu; Sand, Wolfgang (Frontiers in Microbiology, 2020)
Sulfobacillus and Leptospirillum occur frequently in leaching systems. Here we investigated the effects of cells of L. ferriphilum on biofilm formation and leaching performance by S. thermosulfidooxidans. The effects include the presence of L. ferriphilum or an addition of pyrite leachate from L. ferriphilum. Data show that number of attached S. thermosulfidooxidans on pyrite increases, if the pyrite has been pre-colonized by living biofilms of L. ferriphilum, while it decreases if the pre-colonized biofilms had been inactivated. Coaggregation between S. thermosulfidooxidans and L. ferriphilum occurs during the dual-species biofilm formation, but different interactions were noted, if the preculture of L. ferriphilum has been different. If L. ferriphilum had been pre-colonized on pyrite, competition between the two species was noted. However, if the two species were simultaneously inoculated into a sterile leaching system, the interactions between the two species occurred as a kind of mutualism. If S. thermosulfidooxidans performed leaching in a filtered pyrite leachate from L. ferriphilum, the cells preferred to oxidize RISCs instead of ferrous ion and the number of attached cells decreased compared with the control. This result seems to indicate that cells of L. ferriphilum may excrete some kind of signalling metabolite which is effective on cells of S. thermosulfidooxidans causing the latter to use preferentially RISCs. This study gives an indication that in a short-term multi-species leaching system the role of S. thermosufidooxidans may be related with the time when it is introduced to the system.